Upaya Peningkatan Aktivitas dan Hasil Belajar Siswa Kelas VII 6 SMPN 1 Praya Melalui Penerapan Pembelajaran Metode GNT (Guided Note Taking) Tahun Pelajaran 2017/2018 - HM SOSIAWAN (JUPE : Jurnal Pendidikan Mandala, 2019)
This study aims to determine the extent to which the activities and results of mathematics learning in junior high school students of Class VII.6. The type of research is classroom action research. This research was conducted at Praya 1 Public Middle School with 32 students consisting of 16 male students and 16 female students. This study uses a quantitative approach. Analysis of the data used in this study in the form of student activity observation sheets, and student learning outcomes test data. From the results of the study showed an increase in the average activity and student learning outcomes, namely in the first cycle the average value of student activities 11.35 was active, while the average value of student learning outcomes was 67.5 and the percentage of completeness was 81%. In the second cycle the average value of student learning activities 18.2 is categorized as very active, while the average value of student learning outcomes is 70 and the percentage of completeness is 87.5%